2020
DOI: 10.1103/physrevb.102.024508
|View full text |Cite
|
Sign up to set email alerts
|

Conventional isotropic s -wave superconductivity with strong electron-phonon coupling in Sc5Rh6Sn18

Abstract: Sc 5 Rh 6 Sn 18 is a diamagnetic metallic compound (space group: I4 1 /acd, a ≈ 13.5 Å, c ≈ 27.1 Å) which becomes superconducting (sc) at T c = 5.15 K. The sc state was studied on single-crystal samples by temperatureand field-dependent electrical resistivity, specific heat, and muon-spin rotation (μSR) spectroscopy. No anisotropy of the upper critical field B c2 = 7.75 T is observed. Analyses of specific heat indicate enhanced values of the jump [ c p /(γ tot T c ) = 1.58] and of the energy gap ratio [ (0)/(k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
6
11
0
Order By: Relevance
“…On the other hand the local disorder could support such a scenario. This prompted us to perform an additional study of SC properties of Sc 5 Rh 6 Sn 18 , which revealed it to be a conventional SC with stronger electron-phonon coupling and isotropic s-wave gap 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand the local disorder could support such a scenario. This prompted us to perform an additional study of SC properties of Sc 5 Rh 6 Sn 18 , which revealed it to be a conventional SC with stronger electron-phonon coupling and isotropic s-wave gap 41 .…”
Section: Discussionmentioning
confidence: 99%
“…8). It increases with increasing temperature in the direction parallel to ab and almost linearly decreases for ρ c. Such a temperature dependence of ρ(T) could be ascribed to the strong structural disorder and low charge carrier concentration observed in Sc 5 Rh 6 Sn 18 (for more details see discussion in 41 )…”
Section: Electrical and Thermal Transport Propertiesmentioning
confidence: 90%
“…It should be also pointed out that a "semiconductor"-like behavior of ρ(T ) for the non-magnetic germanides and stannides crystallizing with Remeika-like structural arrangement is frequently observed. For instance this is the case for Y 3 Ru 4 Ge 13 , [55][56][57] Lu 3 Rh 4 Ge 13 , 25 Th 3 Ir 4 Ge 13 , 21 Sc 5 Rh 6 Sn 18 58,59 etc. However, such a phenomenon is less clear now.…”
Section: Electrical and Thermal Transport Propertiesmentioning
confidence: 97%
“…In this context, it is of particular interest to examine the superconductivity of weakly correlated centrosymmetric superconductors exhibiting TRS breaking. One such family of superconductors are the caged compounds R 5 Rh 6 Sn 18 (R = Sc, Y, Lu), which crystallize with the tetragonal space group I4 1 /acd [23], and evidence for TRS breaking is found from muon spin relaxation (μSR) measurements [24][25][26] (although TRS breaking signatures were not observed in another study for R = Sc [27]). Resistivity measurements of all three compounds show semiconducting behavior in the normal state, before becoming superconducting below 5.0, 3.0, and 4.0 K for R = Sc, Y, and Lu, respectively [28,29].…”
Section: Introductionmentioning
confidence: 99%